"Comparative evaluation of dentinal penetration of three different endodontic sealers with and without smear layer removal" - Scanning electron microscopic study - K R Sonu; T N Girish; K C Ponnappa; K V Kishan; P K Thameem (Wolters Kluwer Medknow Publications, 2016)
Aim and Objectives: The aim of this study was to test the dentinal tubule penetration of mineral trioxide aggregate (MTA) Fillapex (Angelus, Londria, PR, Brazil), GuttaFlow® 2 sealer (Coltene/Whaledent) with standard sealer AH Plus (Dentsply Detrey, Konstanz, Germany) in instrumented root canals obturated by using cold lateral compaction techniques in either the presence or absence of the smear layer. Materials and Methods: Sixty extracted human mandibular premolars with a single root canal were used for this study. All teeth were prepared using F2 Pro Taper nickel-titanium rotary system. Teeth were randomly divided into three groups of 20 teeth each. GuttaFlow 2, MTA Fillapex and AH Plus were used as sealers in Group I, Group II, and Group III, respectively. Groups were divided into two subgroups in which either the smear layer was removed or retained. Removal of smear layer was achieved by continuous irrigation with 5.25% sodium hypochlorite and 2 ml of 17% ethylenediaminetetraacetic acid. The canals were dried and obturated using respective sealers by cold lateral compaction techniques. After storage at 37°C and 100% humidity for 14 days, the roots were then split into two halves using chisel and mallet. On each section, sealer penetration in the dentinal tubules at cervical, middle, and apical levels was examined by using scanning electron microscope. Results: Sealer penetration into the dentinal tubules was noticed in all groups. AH plus showed deeper penetration, followed by MTA Fillapex and GuttaFlow® 2. The penetration depth of the sealers at the cervical and middle third of root was significantly more than those at apical third. Conclusions: Within the parameters of the present study it was concluded, with the removal of smear layer AH plus sealer showed deeper penetration into the dentinal tubules at cervical and middle third of root compared with apical third.